The Relationship Between Learning Disciplines and Learning Outcome in Food Presentation - Wiken Zelmiyas; Elida Elida; Wiwik Gusnita; Nurhasanah Nurhasanah (Educia Journal, 2026)
Learning discipline is considered one of the essential internal factors influencing students' academic achievement, particularly in vocational education, where both theoretical understanding and practical competencies are required. This study aimed to examine the relationship between learning discipline and students' learning outcomes in the Food Service subject among Grade XI Culinary Arts students at SMK Negeri 1 Ampek Angkek, Indonesia. A quantitative research design employing a correlational approach was adopted. The study involved the entire population of 44 Grade XI Culinary Arts students using a total sampling technique. Primary data on learning discipline were collected through a validated 42-item Likert-scale questionnaire, while secondary data on learning outcomes were obtained from students' official summative assessment records. Prior to hypothesis testing, instrument validity and reliability were established, and data were analyzed using descriptive statistics, normality and linearity tests, and Pearson Product–Moment correlation analysis with IBM SPSS Statistics. The findings revealed that students' learning discipline was generally at a very high level, whereas their learning outcomes were classified as moderate. Assumption testing confirmed that the data were normally distributed and that the relationship between the variables was linear. Pearson correlation analysis demonstrated a positive and statistically significant relationship between learning discipline and learning outcomes (r = 0.845, p < 0.001), indicating a very strong correlation. Furthermore, the coefficient of determination showed that learning discipline explained 71.4% of the variance in students' learning outcomes, while the remaining 28.6% was attributable to other factors not examined in this study. These findings highlight the importance of strengthening students' learning discipline through effective instructional strategies and supportive learning environments to enhance academic achievement and promote competency development in vocational education.